Efektywność solarnej suszarni osadów ściekowych w Żarach = Efficiency of solar sludge dryers in Żary - Myszograj, Sylwia; Panek, Ewa; Wołoszyn, Jerzy (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the technology of solar drying of sewage sludge in wastewater treatment plant in Żary. Analysis of 18 months operation of the system showed that the effect of drying was achieved by 5-fold decrease by weight of sludge. The average moisture of the sludge was 12.3% at the start stage in 2009.
Keywords: osady ściekowe; suszarnia solarna; efektywność; sewage sludge; solar drying; efficiency